Scale-Down Studies of Protein Effects at the Gas-Liquid Interface - Pappas,Konstantinos (2025)
The present study investigated the kinetic stability and activity of water-forming NAD(P)H oxidase (NOX) in a Liebig-type bubble column reactor, simulating industrial-scale conditions at laboratory scale. The study is divided into three parts, examining hydrodynamic parameters, NOX deactivation rate and protein concentration dynamics. The first part investigated and characterized the hydrodynamic phenomena observed in the bubble column reactor at varying gas types (oxygen, air, nitrogen and helium), flow rates (0.05, 0.10 and 0.15 L∙min-1) and sparger diameters (2 mm, 1 mm and porous). Porous spargers with pore diameters less than 0.5 mm significantly enhanced gas holdup (ε), reaching ε=6.2% for oxygen at 0.15 L∙min-1, compared to 4.8% using a 2 mm sparger. The increase in gas holdup corresponded to a higher gas-liquid interfacial area, promoting more efficient mass transfer. The high aspect ratio (AR) defined between length and cross-sectional area of the bubble column (~23), promoted axial dispersion effects and prolonged homogeneous flow profile, increasing gas-liquid interfacial area and limiting bubble coalescing behavior, especially in the use of smaller diameter sparger. Increasing gas flow rate corresponded to high Reynolds bubble number (ReB), turbulence phenomena and low drag coefficient (CD), potentially contributing to the acceleration of NOX deactivation. The second part investigated NOX kinetic activity and stability at the same conditions. Smaller sparger designs reduced NOX biocatalytic deactivation and improved kinetic stability, increasing NOX half-life from 18.4 to 21.4 hours when switching from 2 mm to porous sparger at 0.15 L∙min-1. The third part examined NOX protein concentration changes using different gas types at varying gas flow rates and sparger diameters. NOX protein displayed higher concentrations across decreasing sparger dimensions at 0.15 L∙min-1 in oxygen bubbling, while increased flow rates in nitrogen and helium bubbling accelerated protein losses. A strong positive correlation (ρ=0.76) between kLa and the normalized NOX concentration decay rates indicated that mass transfer effects were potentially linked with the complex hydrodynamic phenomena participating in NOX protein losses. This comprehensive investigation enhances understanding of NOX behavior at gas-liquid interfaces and contributes to optimizing biocatalytic processes in bubble column reactors.
Keywords: NAD(P)H Oxidase; Bubble Column Reactor; Gas-Liquid Interface; Enzyme Deactivation; Mass Transfer; Biocatalysis; Hydrodynamics; Biotechnology